The synergistic effect of ultrasonic activation and irrigation on Enterococcus faecalis biofilm - Abeer A Al-Mahdi; Hanan A Balto (Wolters Kluwer Medknow Publications, 2016)
Aim: The aim of this investigation was to compare the efficacy of passive ultrasonic irrigation (PUI) with either 2.5% sodium hypochlorite (NaOCl) or saline, with that of conventional syringe irrigation on intraradicular Enterococcus faecalis biofilm. Materials and Methods: Biofilms of E. faecalis were established over 21 days in 80 single roots that had undergone biomechanical preparation followed by gamma radiation. Biofilms were treated for 1 min with 2.5% NaOCl/PUI (Group 1), 2.5% NaOCl (Group 2), sterile saline/PUI (Group 3), and sterile saline (Group 4). The positive control (n = 4) was used to confirm the presence of biofilm before various treatments. Additional four samples that served as a negative control were used to confirm the sterility of the samples. Biofilm eradication was evaluated by Colony Forming Unit (CFU) quantification and scanning electron microscopy (SEM). Results: The median of CFUs of S1 was significantly higher than that of S2 in all experimental groups. SEM examination showed a significant difference between the positive control and the experimental groups (P < 0.001), with the highest score of biofilm in the positive control group followed by Group 4 and both groups were not statistically significant from each other (P = 0.067). Following various treatments, the highest scores of biofilm were observed in the coronal third and the least were in the apical third. Conclusions: PUI did not increase the effectiveness of NaOCl irrigation on biofilm removal, however, PUI enhanced biofilm disturbance when used with saline. The least mean score of remaining biofilm was in the apical third of all treatment groups compared to other thirds.